Training Faculty for Better Online Teaching â€“ Need & Issues - Pai, Chiplunkar (Journal of Engineering Education Transformations, 2022)
Online teaching and learning is a necessity rather than a choice in all forms of education today. Faculty are one of the important element in this online teaching / learning process. There are several issues pertaining to faculty and one important issue is the training of the faculty and their orientation towards online teaching. There are several platforms, services and MOOCs available, which provide training to faculty regarding different aspects related to teaching better online. This paper explores the need for training the faculty to do better online teaching. The author has conducted a 4-hour short course on â€œonline learning â€“ theory and practiceâ€ for 23 faculty in his institution. Feedback collected from the faculty through a questionnaire survey support the need for such training by emphasizing the need to understand both theoretical and practical aspects, but expect freedom in selection of the platform to be used, consider student satisfaction and delivery as more important, support online assessment and consider regular student feedback important for online teaching. The findings of this study have some implications for development and implementation of training and support programs to help faculty to teach online.